Lexical-semantic Features of Color Spectrum in M.А. Bulgakov’s Novel “The Master and Margarita”: The thematic groups "Black" and "White" as Models - Ali, Najwa F. (Al-Adab Journal, 2019)
The article analyzes the structure-forming function and stylistic characteristics of the color naming of the thematic groups “Black” and “White” in M. Bulgakov’s novel "Master and Margarita". The subject of the research is the writer’s idiolect. A multidimensional analysis of the vocabulary denoting color has been constructed: particular features of color names are considered, word-formation models are described, semantic transformations and symbolic meanings are also described, and the role of color terms in the novel’s figurative system has been analyzed.